Low-cost solution of LED driving, designed for tunable white lighting systems. Issue 6 (2018) - Hrbac, Roman; Kolar, Vaclav; Novak, Tomas; Prokop, Lukas; Vanus, Jan
Abstract: Aiming at increased lighting comfort, new types of light fixtures may currently be seen that may not only be dimmed, but can also adjust the temperature of the light. The ability to adjust the brightness and color temperature is not only supposed to create a pleasant atmosphere, but it may also have a positive effect on human organism, especially if luminaries can be controlled to get as close as possible to the dynamics of natural light. The change in color temperature is known to affect the production of the melatonin hormone in the human body. This capacity is especially useful in situations where we need to increase the alertness of people working at night and thus increase their performance when carrying out certain tasks. This paper deals with the design of a low-cost solution for the power supply units of LED light fittings able to adjust the brightness and temperature of light aiming to achieve the best electrical parameters. While working on the design, the possibility of adding other electronic components to the power supply was considered, which would further increase its usefulness in the future. Experimental results of the power supply efficiency measurements for different control frequencies are presented.